Customer Experience and Customer Engagement in Relationship with Customer Loyalty During Black Swan Events Covid-19 - Baskara, Andika; Pranaditya, Ari (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The aim of the research was to determine the effect of customer experience and customer engagement in relationship with customer loyalty during the Black Swan Events Covid-19. The population was visitors at tourist sites in Semilir Village, Semarang Regency, with as many as 100 people. The study used the purposive sampling technique to obtain data. Based on the research, it was found that there was a significant positive effect between the experimental customer variable and the customer engagement variable on the interest in revisiting. The results of the test obtained the score of r square for revisit interest of 0.561, which means that interest in revisiting is influenced by customer experiential and customer engagement by 56.1%.